Umi Matsuzaki’s representation of war trauma: A semiotic approach to Studio Ghibli’s From Up on Poppy Hill - Wedhowerti, Wedhowerti (citeus, 2025)
Japanese films that explore war trauma are relatively rare, and this research departs from that gap by analyzing Studio Ghibli’s From Up on Poppy Hill. The film reflects the conscience of Japanese society by depicting the realities of post-war life in the 1960s. Using a qualitative descriptive approach, this study examines how the main character, Umi Matsuzaki, represents war trauma through eight selected scenes and how such trauma encodes myth. By applying Roland Barthes’ semiotic theory, the findings reveal that Umi embodies symptoms of post-traumatic stress disorder (PTSD), manifested primarily through avoidance and intrusion. Her trauma is deeply rooted in the loss of her father during the Korean War, which becomes a recurring source of psychological distress. Specific symptoms identified include her reluctance to speak about her father, involuntary memories embodied in his shadow, nostalgic recollections of raising signal flags as he once taught her, distressing dreams of meeting him, recurrent war imagery such as the explosion of his supply ship, and prolonged psychological suffering. These elements demonstrate that the myth of war trauma extends beyond collective national memory into intimate family experiences. Ultimately, the study highlights how From Up on Poppy Hill not only portrays post-war recovery but also reinforces the pervasive impact of unresolved war trauma in Japanese cultural narratives.